Recent advances in cassava pest management - Bellotti, Anthony C.; Smith, L.; Lapointe, Stephen L. (Annual Reviews, 1999)
Cassava (Manihot esculenta) occupies a uniquely important position as a food security crop for smallholder farmers in areas of the tropics where climate, soils, or societal stresses constrain production. Given its reliability and productivity, cassava is the most important locally produced food in a third of the world's low-income, food-deficit countries. It is the fourth most important source of carbohydrates for human consumption in the tropics, after rice, sugar, and maize. World production of cassava from 1994 1996 averaged 166 million tons/year grown on 16.6 million hectares (ha), for an average yield of 9.9 tons/ha. Approximately 57% is used for human consumption, 32% for animal feed and industrial purposes, and 11% is waste. Africa accounts for 51.3% of the production; Asia, 29.4%; and Latin America, 19.3%. The area planted to cassava in Africa, Asia, and Latin America is 10.3, 3.7, and 2.6 million ha, respectively.